The relationship between body temperature and diet on typhoid fever among toddlers aged 3 – 5 years - Purnamasari, Anisa; Prima, Ashar; Harahap, Desrinah; Andas, Amzal Mortin (Palembang MediRose Publisher, 2022)
Background: Typhoid fever is a significant health problem in many countries. Globally, it is estimated that 21 million toddlers suffer from this disease each year. Purpose: This research aimed to analyze the relationship between handling body temperature and diet on the length of stay for typhoid fever among toddlers. Methods: This research was a cross-sectional study design. The population in this study were 87 toddlers with typhoid fever Lepo-Lepo Health Care Center. The sampling technique was purposive sampling and obtained a total sample of 46 children under five. Results: We found that Treatment of body temperature on length of stay (X2 = 5.642; p = 0.003) and diet management on length of stay (X2 = 4.920; p = 0.001) at the level of confidence 95% (? = 0.05). It means that there is a relationship between handling body temperature and diet with the length of stay in toddlers with typhoid fever. Conclusions: This study provides information about the body temperature and diet contributing to toddlers with typhoid fever. Clinical and community nursing can provide intervention by considering temperature and diet.